2004
DOI: 10.1038/sj.ijo.0802735
|View full text |Cite
|
Sign up to set email alerts
|

Relation of BMI to fat and fat-free mass among children and adolescents

Abstract: OBJECTIVE:Although the body mass index (BMI, kg/m 2 ) is widely used as a surrogate measure of adiposity, it is a measure of excess weight, rather than excess body fat, relative to height. We examined the relation of BMI to levels of fat mass and fat-free mass among healthy 5-to 18-y-olds. METHODS AND PROCEDURES: Dual-energy X-ray absorptiometry was used to measure fat and fat-free mass among 1196 subjects. These measures were standardized for height by calculating the fat mass index (FMI, fat mass/ht 2 ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
382
6
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(415 citation statements)
references
References 37 publications
18
382
6
9
Order By: Relevance
“…Higher body fat in girls was probably responsible for higher BMI, especially beyond 14 þ years. A similar observation has been reported by Freedman et al (2005) who have estimated body fat using DEXA. The fact that these trends in body fat are observed in adolescents from White population and also confirmed in Indian Overweight adolescents and hypertension S Rao et al population, gives us confidence in the estimates of body fat based on BIA.…”
Section: Discussionsupporting
confidence: 87%
“…Higher body fat in girls was probably responsible for higher BMI, especially beyond 14 þ years. A similar observation has been reported by Freedman et al (2005) who have estimated body fat using DEXA. The fact that these trends in body fat are observed in adolescents from White population and also confirmed in Indian Overweight adolescents and hypertension S Rao et al population, gives us confidence in the estimates of body fat based on BIA.…”
Section: Discussionsupporting
confidence: 87%
“…36 In this study we could observe that for a similar BMI value for age, girls and boys are different in relation to body composition, indicated by a significant higher BF% in girls. In a 7.5-year longitudinal study, Wen et al 6 showed that increases in fat mass explained the increases in CRP levels during pubertal growth of Finnish girls but not vice versa.…”
Section: Discussionmentioning
confidence: 63%
“…When looking for the nutritional status in individuals, it is important to assess not only BMI values but also the body composition (Maynard et al, 2001). Even though the BMI is the most widely used measurement to define obesity, it has limitations on an individual level and is only a proxy measurement of body fat (Daniels et al, 1997;Freedman et al, 2005). Two persons with the same amount of body fat can have quite different BMI values, because BMI reflects not only body fat, but also bone, muscle and other lean tissues (Ellis et al, 1999).…”
Section: Boys Girlsmentioning
confidence: 99%